PENGARUH STORY TELLING PADA ANAK USIA SEKOLAH DENGAN KESULITAN MAKAN SAYUR DI SDN INPRES MANGARAN - Kasehug, Ivana (Journal Of Community & Emergency, 2024)
School age which is 7-11 years old is a period of intense social, intellectual and emotional development for children. Children need nutrition adequate to achieve optimal growth and development, therefore nutrition has an important role ffor growth and development where nutritients are obtained from food consumed every day. In this study, the researcher used a method namely by distributing questionnaires which contain research on vegetable pictures vegetables and the benefits of vegetables. Statistical test results using the independent t test obtained p-value =0,002 which menas Ha is accepted and H0 is rejected, namely there is a significant influence between story telling in school-age children with difficulty eating vegetables at SDN Inpres Mangaran. There is an influence between story telling in scholl-age children with difficulty eating vegetables at SDN Inpres Mangaran. It is recommended for parents to always teach their children to live healthy that is by giving food such an vegetables to children later tell me why you have to eat vegetables so that the child will get used to it eat vegetables every day.